Innovative communication approaches for initializing pediatric palliative care: perspectives of family caregivers and treating specialists - Hrdlickova, Lucie; Polakova, Kristyna; Loucka, Martin (BMC palliative care, 2023)
BACKGROUND: Effective cooperation between a pediatric palliative care team (PPCT), primary treating specialists, patients and families is crucial for high quality care of children with complex life-limiting conditions. Several barriers among patients, families and treating specialists have been identified in the context of initializing pediatric palliative care. The aim of the study was to assess the experience with initial pediatric palliative care consultations from perspectives of family caregivers and treating physicians with a special focus on two innovative approaches: attendance of the treating specialist and the opportunity for parents to give feedback on the written report from the consultation. METHODS: This was a qualitative study using semi-structured interviews with family caregivers of children with malignant and non-malignant disease and their treating specialists. Framework analysis was used to guide the data collection and data analysis. RESULTS: In total, 12 family caregivers and 17 treating specialists were interviewed. Four main thematic categories were identified: (1) expectations, (2) content and evaluation, (3) respect and support from the team and (4) consultation outcomes. Parents viewed the consultation as a unique opportunity to discuss difficult topics. They perceived the attendance of the treating specialist at the initial consultation as very important for facilitating communication. Treating specialists valued the possibility to learn more about psychosocial issues of the child and the family while attending the initial palliative care consultation. All participants perceived the written report from the consultation as useful for further medical decisions. Family members appreciated the chance to give feedback on the consultation report. CONCLUSIONS: Our study identified several clinically relevant issues that can help initialize pediatric palliative care and establish effective collaboration between families and PPCT and treating specialists. Supporting treating specialists in their ability to explain the role of palliative care is important in order to reduce the risk of misunderstanding or unrealistic expectations. Developing more specific expectations seems to be one of the ways to further increase the effectiveness of initial consultations. The results of the study can be especially helpful for the initial phase of implementing pediatric palliative care and initializing the process of setting up a collaborative relationship with palliative care teams in the hospital.
Keywords: Family; komunikace; Parents; Child; Palliative Care; lidé; Qualitative Research; rodina; dítě; osoby pečující o pacienty; paliativní péče; Caregivers; Communication; kvalitativní výzkum; rodiče; Humans